Pelatihan Pembuatan Bakso Sehat bagi Ibu Rumah Tangga Desa Mamala Kabupaten Maluku Tengah - Pramita Wally; A Abdollah; A S Marwah; I S. S Sohilauw; A Wahyudi (IAIN AMBON, 2022)
Healthy meatballs are meatballs that are processed without using food preservatives by paying attention to adequate sanitation quality so as to produce hygienic meatball products. Processing of healthy meatballs from fish can be done yourself, starting from processing raw materials to the appropriate boiling process in order to avoid bacteria that cause disease infections due to bacterial contamination, considering that meatballs are one of the processed products that are very popular with the public. Healthy meatballs from fish are safe for consumption because they have high nutritional value so that they can increase their selling value in the market. household economic value. Activities are carried out using the method of material presentation, discussion and practice. The result of this service is increasing public awareness in producing and consuming healthy natural processed products and the creation of fish ball products with a mixture of natural ingredients as preservatives so as to improve the quality of meatballs free from bacterial contamination. There is a need for the sustainability of this activity, especially the existence of innovation training or diversification of other food products so that they are worthy of being used as products in the development of small and medium enterprises in order to increase income to help the household economy.Keywords: Healthy Meatballs, Celery, Entrepreneur